Prospects of activation of Russian companies entering the IPO market - E. I. Kulikova (Путеводитель предпринимателя)
Exploring the mechanisms of raising funds by Russian companies, the author predicts the activation of the Russian IPO/SPO market and identifies the main problems that need to be solved for its development.